Muslims in Motion Islam and National Identity in the Bangladeshi Diaspora. - Kibria, Nazli (New Brunswick, NJ : Rutgers University Press, 2011)
Muslims in Motion provides a comparative look at Bangladeshi Muslims in different global contexts-including Britain, the U.S., the Middle East, and Malaysia. Nazli Kibria examines international migrant flows from Bangladesh, and considers how such migrations continue to shape Islamization in these areas. Having conducted more than 200 in-depth interviews, she explores how, in societies as different as these, migrant Muslims, in their everyday lives, strive to achieve economic gains, sustain community and family life, and realize a sense of dignity and honor.
Figures and Tables; Preface and Acknowledgments; 1. Muslim Migrants, Bangladeshis Abroad; 2. Bangladesh: Nationalism, Islam, and International Migration; 3. Bangladeshi American Dreams; 4. Becoming Muslim American; 5. British Bangladeshis: Changing Transnational Social Worlds; 6. Muslim Encounters in the Global Economy; 7. Muslim Migrants: National Origins and Revivalist Islam; Notes; Bibliography; Index; About the Author.
Description based on print version record.
Keywords: Bangladesh -- Emigration and immigration; Bangladeshis -- Great Britain; Bangladeshis -- United States; Social Science; History; Bangladeshis -- United States; Bangladeshis -- Great Britain; Bangladesh -- Emigration and immigration; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; HISTORY / United States / State & Local / General; Electronic books